Sauraja Pattojo: Private House of Queen of Ke-Datu-An Pattojo XII - Andi Abidah; Erich Lehner (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2021)
Pattojo is a small kingdom in the past, and at this time, Pattojo was called village of Pattojo. The Kingdom of Pattojo is also called ke-datu-an Pattojo whose the king or queen was called datu. To be a king or queen, one must of the highest Nobel or Datu title. Bugis house is identical to the stilt on the house and the rectangular facet is elongated. The house's mention in the bugis tribe has a difference between the noble house and the ordinary people's house. The noble house is called saoraja (Sao=house, raja=big so that saoraja is a big house), and the people's house is called the bola. Generally, noble houses in ancient times were larger than ordinary people's houses. This research is a study on the form of Bugis noble house or king's private house (saoraja datu pattojo: local language) built before Indonesia's independence. The form of façade the arrangement of space in the house has nothing in common with the original Bugis house. It may indicate that the king's house did not follow the original form of Bugis house but has combined between the Bugis and European architecture. Some things that are very clearly undergoing a change from the original of Bugis house is the roof, position of the stairs, there is an arc shape on the underside of the house, and the arrangement of the room has also undergone changes.